Model Evaluasi Pendidikan Islam: Analisis Literatur Menuju Transformasi Pembelajaran Humanis - Saputra, Remon; Putri, Sri Wahyuni Eka; Ruzzaman, Kamal; Maryani, Maryani; Amra, Abhanda (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This article aims to describe the concepts, principles, and application of evaluation in Islamic education as an important part of efforts to ensure the quality of education in line with Islamic values. This study also aims to identify the challenges of evaluation in the digital age and offer directions for developing a more adaptive and relevant evaluation model for Islamic educational institutions. This study uses a descriptive qualitative method with a literature study approach. Data was obtained through searching and analysing various sources, such as books, scientific articles, regulations, and reports related to evaluation practices in Islamic education. The analysis was carried out by examining the suitability of theories, principles, and empirical findings to understand the patterns, weaknesses, and opportunities for evaluation development. The results of the study show that evaluation in Islamic education not only assesses cognitive aspects but also covers the affective and psychomotor domains in accordance with the holistic objectives of education. Evaluation needs to be carried out in a continuous, fair, comprehensive manner and based on spiritual values that emphasise honesty, responsibility, and accountability. This study also emphasises the importance of adaptive evaluation models in the digital age through the use of artificial intelligence and digital literacy to improve the accuracy, efficiency, and objectivity of assessment.